2015
DOI: 10.7860/jcdr/2015/10478.5396
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Characteristics of Persistent Vegetative State Due to Prolonged Hypoglycemia

Abstract: Hypoglycemia is the sudden decrease in serum glucose level <50mg/dL. Neurological manifestations complicating profound and prolonged hypoglycemia range from reversible focal deficits and transient encephalopathy to irreversible coma. Here, we report magnetic resonance imaging characteristics of a patient with prolonged hypoglylicemia. A 47-year-old woman with a history of insulin dependent diabetes mellitus has been brought to the emergency room by her relatives. She used mistakenly overdose insulin injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Hypoglycemia-related neurologic and mental disorders known as hypoglycemic encephalopathy (HE) have been recognized since the 1920s. Hypoglycemia is defined as an abrupt diminution in blood glucose level <50 mg/dL [1] . Hypoglycemia is usually observed in chronic alcoholism, severe metabolic disorders, or in patients treated for diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoglycemia-related neurologic and mental disorders known as hypoglycemic encephalopathy (HE) have been recognized since the 1920s. Hypoglycemia is defined as an abrupt diminution in blood glucose level <50 mg/dL [1] . Hypoglycemia is usually observed in chronic alcoholism, severe metabolic disorders, or in patients treated for diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the diagnosis of vegetative state depends on expert observation of the patient's behavior [10]. Although recent studies have shown the prognostic value of the structure of the resting-state electroencephalogram and resting-state networks [11,12], there are limited molecular prognostic markers available to predict the chance of recovery or the risk of serious consequences. Therefore, further efforts are needed to investigate the molecular mechanisms underlying the vegetative state and to develop molecular diagnostic/prognostic markers for the vegetative state.…”
Section: Introductionmentioning
confidence: 99%